Mówca czy autoplagiator? W poszukiwaniu „książki miejsc wspólnych” Piotra Skargi - Komorowska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Piotr Skarga lived and wrote in a period when ars rhetorica had an enormous influence on reading habits and writing strategies. In the course of reading many later authors took notes in their so called commonplace books — quotations, systematically ordered, were later at hand and ready to use in their writings. Analysis of some parts of Skarga’s writings — i.e. repetitions of exempla and topoi — shows that he probably had his own commonplace book. The article examines a possibility of recreating its fragments and puts Skarga’s writings in the context of 16th/17th century popularity of printed and self-made compilations of commonplaces.